Impactos de complexos de rutênio (II) em diferentes abordagens da agregação do peptídeo beta amiloide - Tiburcio, Marco Antonio (2025)
Alzheimer's Disease is the most common form of dementia, with projected costs of $1 trillion by 2030. Its main features include deposits of the Aβ peptide and neurofibrillary tangles of the tau protein. Increased life expectancy is linked to the rising incidence of the disease, creating significant social and financial impacts. This study aims to evaluate the effects of Ru(II) complexes as modulators of Aβ aggregation in different approaches, from heterogeneous aggregation with insulin to in vivo applications. The modulating effect of the RuApy complex on cross-aggregation between Aβ and insulin was monitored through Tyr10 emission, circular dichroism (CD), and AFM. Emission spectra for Aβ showed suppression of Tyr-OH emission (300 nm) in favor of Tyr-O¯ ion formation (340 nm), a behavior not observed in the presence of insulin and the RuApy complex. CD and AFM analyses revealed the formation of amorphous aggregates instead of the fibrils typically seen with Aβ. The aggregates formed in the Aβ/Insulin and Aβ/Insulin/RuApy interactions were less toxic compared to Aβ aggregates when tested on SH-SY5Y neuroblastoma cells. In another approach, the influence of the RuNDI complex on Aβ aggregation was monitored by nephelometry, CD, and TEM. The presence of the RuNDI complex significantly reduced relative nephelometry units and suppressed β-sheet signals in CD spectra, indicating reduced aggregate formation. TEM images revealed the formation of amorphous aggregates. The effects of the RuNDI complex on Aβ aggregation were also evaluated in APP/PS1 mice, a model for Alzheimer's Disease. These animals develop Aβ deposits in the cortex and hippocampus after 16 weeks of age. The complex was administered intraperitoneally at daily doses of 1 mg/kg for 10 weeks. Amyloid deposition was monitored in real-time using multiphoton microscopy. ELISA and immunofluorescence assays were performed on blood and cortex samples at the end of the experiments. Although real-time disease progression could not be assessed, lower levels of Aβ40/42 were observed in cortex samples from treated mice. Immunofluorescence using ThS and 4G8 showed that the RuNDI complex did not affect the size of existing plaques but significantly reduced plaque density and load in the cortex and hippocampus. These observations demonstrate that the RuApy and RuNDI complexes directly impact Aβ fibrillation in different approaches, leading to the formation of amorphous and non-toxic fibrils and reducing the formation of deposits in critical brain areas of transgenic mice.